Adopting exergy analysis for use in aerospace - Hayes, David; Lone, Mudassir; Whidborne, James F.; Camberos, José; Coetzee, Etienne (Elsevier, 2017)
Thermodynamic analysis methods, based on an exergy metric, have been developed to improve system efficiency of traditional heat driven systems such as ground based power plants and aircraft propulsion systems. However, in more recent years interest in the topic has broadened to include applying these second law methods to the field of aerodynamics and complete aerospace vehicles. Work to date is based on highly simplified structures, but such a method could be shown to have benefit to the highly conservative and risk averse commercial aerospace sector. This review justifies how thermodynamic exergy analysis has the potential to facilitate a breakthrough in the optimization of aerospace vehicles based on a system of energy systems, through studying the exergy-based multidisciplinary design of future flight vehicles.
Keywords: Exergy; Thermodynamics; Multi disciplinary optimisation